Ảnh hưởng của sự tự nhiên chào đón, sự cam kết cộng đồng và lợi ích kinh tế cá nhân đến thái độ và hành vi ủng hộ sự phát triển du lịch của người dân tại Việt Nam - Pham To Thuc , Han (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
On the basis of Social Exchange Theory, Theory of Reasoned Action, and Emotional Solidarity Theory, this study explores a comprehensive picture of the relationship between economic and non-economic factors with resident’s attitudes and behavior to support the tourism development in 10 developing tourism provinces of Vietnam. The study is conducted in two phases: Qualitative and quantitative. Structural Equation Modeling (SEM) is employed to test the appropriateness of the model and research hypotheses. The results obtained from data collected from 534 local people affirm positive relationships among the elements of welcoming nature, community commitments, personal economic benefits to pro-tourism development attitudes and behavior (except community commitments do not affect pro-tourism development behavior), as well as pro-tourism development attitudes to pro-tourism development behavior.